ANALYSIS OF WATER AVAILABILITY IN THE KAMPUNG BANJAR RESERVOIR AND KEBUN RAYA RESERVOIR IN BANJARBARU CITY FOR MEETING WATER NEEDS - Alifa, Salsabila Zata; Novitasari, Novitasari; Sofia, Elma (CERUCUK, 2025)
The Kampung Banjar Reservoir and Kebun Raya Reservoir were built to address the disrupted water catchment areas caused by land clearing for the development of the South Kalimantan Province Government office area in Banjarbaru. These two reservoirs are planned to function as water catchment areas, water tourism destinations, and raw water sources within the office areas. The water availability in the reservoirs is expected to remain stable. Therefore, a study on the water availability analysis of both reservoirs is necessary to ensure that the stored water can be utilized optimally and sustainably, particularly for tourism purposes. The research methodology includes data collection, data analysis, results, and discussion. The analysis phase involves evapotranspiration analysis, water availability analysis using the F. J. Mock method, and dependable flow analysis. Based on the flow simulation calculations using the F. J. Mock method, a 90% dependable flow was selected for raw water rEquationuirements. The largest dependable flow occurs in December, with a flow value of 0.1557 m³/second for the Kampung Banjar Reservoir and 0.2028 m³/second for the Kebun Raya.  Keywords: Water Availability, Dependable Flow, Kampung Banjar Reservoir, Kebun Raya Reservoir.